Nuptiality of Ageing Population Affect the Mental Health: A Longitudinal Study - Maretalinia Maretalinia; Cucu Herawati; Awis Hamid Dani (JURNAL INFO KESEHATAN, 2025)
The phenomenon of increasing numbers of elderly people is a demographic challenge that has a wide impact, especially on their physical, mental, social and economic health. This study aims to trace changes in marital status and its relationship to the incidence of depression in the elderly in Indonesia. This study used secondary longitudinal data from the Indonesian Family Life Survey (IFLS) waves 4 and 5, with elderly respondents aged >60 years who had complete data on marital status, depression, and other covariates. The dependent variable is depression which assessed using the Centers for Epidemiologic Studies Depression Scale (CES-D 10). The main independent variable was changes in marital status, accompanied by control variables such as age, gender, place of residence, and religion. Data were analyzed in a wide format using univariate, bivariate (Chi-square and t-test), and binary logistic regression. The findings of this study showed that 9.07% of elderly people experienced depression at the time of the follow-up study. The changes in marital status, age, and place of residence were significantly related to depression, while gender and religion did not show a significant relationship. Elderly who changed their marital status from married to divorced/separated/widowed/widower had a lower risk of depression, higher age decreased the likelihood of depression, while living in rural areas increased the risk. Gender and religion were not significantly associated with the incidence of depression. Interventions such as psychosocial support and mental health-based programs that take into account factors such as changes in marital status, age, and place of residence are needed.